Residents’ perceptions of an integrated longitudinal curriculum: a qualitative study - Lubitz, Rebecca; Lee, Joseph; Hillier, Loretta (Canadian Medical Education Journal, 2015)
Background: The purpose of this study was to explore family medicine residents’ perceptions of a newly restructured integrated longitudinal curriculum. Method: A purposeful sample of 16 family medicine residents participated in focus group interviews conducted from a grounded theory perspective to identify the characteristics of this training model that contribute to and that challenge learning. Results: Eight key themes were identified: continuity of care, relevance to family medicine, autonomy, program-focused preparation, professional development as facilitated by role modeling, patient volume, clarity of expectations for learners, and logistics. Positive learning experiences were marked by high levels of autonomy, continuity, and relevance to family medicine. Less favorable learning experiences were characterized by limited opportunities for continuity of care, limited relevance to family medicine practice and unclear expectations for the resident’s role. Family physician-led learning experiences contributed to residents’ understanding of the full scope of family medicine practice, more so than specialist-led experiences. The logistics of implementing the integrated block were challenging and negatively impacted continuity and learning. Conclusions: This study suggests that an integrated longitudinalized family medicine block training model has the potential to support the principles of a longitudinal integrated competency-based curriculum to effectively prepare residents for family medicine practice.